2017
DOI: 10.1016/s2468-1253(16)30206-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of psychological therapy on disease activity, psychological comorbidity, and quality of life in inflammatory bowel disease: a systematic review and meta-analysis

Abstract: Article:Gracie, DJ orcid.org/0000-0001-9616-981X, Irvine, AJ, Sood, R et al. (3 more authors) (2017) Effect of psychological therapy on disease activity, psychological comorbidity, and quality of life in inflammatory bowel disease: a systematic review and meta-analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
145
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(160 citation statements)
references
References 53 publications
2
145
0
4
Order By: Relevance
“…Also, there was little or no evidence of the cost‐effectiveness of online CBT intervention. These results are contradictory with a recent systematic review which showed that depression scores and quality of life in IBD patients might be improved in the short‐term after psychological therapy intervention, particularly CBT, and identified the efficacy gap between online and F2F psychotherapy modalities . This suggests that human contact might be necessary for psychotherapy to improve the outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…Also, there was little or no evidence of the cost‐effectiveness of online CBT intervention. These results are contradictory with a recent systematic review which showed that depression scores and quality of life in IBD patients might be improved in the short‐term after psychological therapy intervention, particularly CBT, and identified the efficacy gap between online and F2F psychotherapy modalities . This suggests that human contact might be necessary for psychotherapy to improve the outcomes.…”
Section: Discussionmentioning
confidence: 67%
“…Patients diagnosed with IBD face the prospect of a lifelong medical condition with a heterogeneous, unpredictable and potentially debilitating disease course [10]. IBD is associated with psychological stress, depression and anxiety as well as increased risk of psychological comorbidities [11, 12]. The disease often imposes a considerable symptom burden and significantly impacts the patient’s daily life and HRQoL [13].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that it is this subgroup of patients with significant levels of distress who benefit most from psychological intervention. The results of the majority of previous RCTs suggest that CBT has limited effect on self‐reported disease course for people with IBD without disturbance to mood (Gracie et al, ). Based on our findings, future RCT may show improved disease‐related outcomes if participants with clinically significant symptoms of anxiety and low mood are recruited.…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews have been published that have examined the impact of psychotherapy on biopsychosocial outcomes for people with IBD (Gracie et al, ; Knowles et al, ; McCombie, Mulder, & Gearry, ; Timmer et al, ). A Cochrane meta‐analysis of randomized controlled trials (RCTs) concluded that there was no evidence that psychological interventions enhanced emotional states, quality of life (QOL), or reduced disease activity in the short‐term or at 12 months in unselected adults with IBD.…”
Section: Introductionmentioning
confidence: 99%